Pelatihan Edukasi Pola Asuh Anak Dalam Pendidikan Menuju Keluarga Sakinah di Era Disrupsi - Winda Ayu Dyah Saputri; Muta'al Anafiah; Antsya Zhadka Anaztha; Reza Marlinandhani; Mustiko Wahyu Wiratmoyo; Ahmad Khaniffuddin; Faiz Rahmawati (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2026)
This community service activity is motivated by the low level of parenting literacy, particularly in addressing the challenges of the disruption era marked by rapid digital technological development and limited parental understanding in the aspects of education, law, and family management. This program aims to enhance parents’ knowledge and awareness in implementing appropriate parenting practices to support the realization of a sakinah family. The methodology employed is a descriptive qualitative approach, including stages of problem identification, data collection and analysis, program planning, implementation of educational seminars, interactive discussions, and evaluation. The results indicate an increase in participants’ understanding of democratic parenting, child protection from a legal perspective, and effective family management, including supervision of children's digital technology use. The discussion highlights that an integrative approach based on education, law, and family management strengthens parenting literacy and improves family communication quality. The novelty of this program lies in its multidisciplinary integrative educational model that is adaptive to the digital era. The implications suggest the need for strengthening sustainable and collaborative community-based parenting education policies to enhance family resilience.